2021
DOI: 10.1098/rspb.2020.2379
|View full text |Cite
|
Sign up to set email alerts
|

Mesocarnivore community structuring in the presence of Africa's apex predator

Abstract: Apex predator reintroductions have proliferated across southern Africa, yet their ecological effects and proposed umbrella benefits of associated management lack empirical evaluations. Despite a rich theory on top-down ecosystem regulation via mesopredator suppression, a knowledge gap exists relating to the influence of lions ( Panthera leo ) over Africa's diverse mesocarnivore (less than 20 kg) communities. We investigate how geographical variation in mesocarnivore community richness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 74 publications
4
6
0
Order By: Relevance
“…The fact that several African carnivores were involved in IGK events as both the aggressor and the victim challenges the classic two‐rank view on mesopredator suppression (Prugh et al 2009) and lends further support to potential multilevel cascading effects in species‐rich carnivore guilds (Levi and Wilmers 2012). In addition, the observed prevalence of large‐to‐small IGK events expands the multilevel theory by suggesting possibly stronger than predicted net suppressive effects of large carnivores, as highlighted by Prugh and Sivy (2020) and suggested empirically for lion suppression of African mesocarnivore species (Curveira‐Santos et al 2021 b ). We encourage future research that revisits top‐down structuring of carnivore guilds in other species‐rich systems containing large hyperpredatory carnivores (e.g., tiger [ Panthera tigris ] and leopard in Southern Asia or jaguars [ Panthera onca ] and pumas [ Panthera concolor ] in South America).…”
Section: Discussionsupporting
confidence: 64%
“…The fact that several African carnivores were involved in IGK events as both the aggressor and the victim challenges the classic two‐rank view on mesopredator suppression (Prugh et al 2009) and lends further support to potential multilevel cascading effects in species‐rich carnivore guilds (Levi and Wilmers 2012). In addition, the observed prevalence of large‐to‐small IGK events expands the multilevel theory by suggesting possibly stronger than predicted net suppressive effects of large carnivores, as highlighted by Prugh and Sivy (2020) and suggested empirically for lion suppression of African mesocarnivore species (Curveira‐Santos et al 2021 b ). We encourage future research that revisits top‐down structuring of carnivore guilds in other species‐rich systems containing large hyperpredatory carnivores (e.g., tiger [ Panthera tigris ] and leopard in Southern Asia or jaguars [ Panthera onca ] and pumas [ Panthera concolor ] in South America).…”
Section: Discussionsupporting
confidence: 64%
“…However, particularly in the protected area, small carnivore species tended to spatially avoid lions. This is in line the with recently uncovered susceptibility of small African carnivores to lion suppression (Curveira‐Santos et al, 2022 ; Curveira‐Santos, Sutherland, Tenan, et al, 2021b ). Unlike larger subordinate species, better equipped to escape and mitigate dangerous encounters while co‐occurring with the apex predator, for small carnivores spatial avoidance of lions may be a better strategy (Wirsing et al, 2010 ).…”
Section: Discussionsupporting
confidence: 90%
“…Changes in guild composition are accompanied by varying levels of human disturbance and its influence on resource availability across multiple land uses. Together, these can deeply shape the structure of carnivore assemblages (Curveira‐Santos, Sutherland, Tenan, et al, 2021b ; Schuette et al, 2013 ) and potentially alter the underlying network of species interactions and community regulation pathways (Dorresteijn et al, 2015 ). Nonetheless, context‐dependent changes in carnivore assemblages have received little attention in carnivore‐rich regions of southern Africa, where context‐dependency is likely to have profound effects.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have assessed spatial patterns of such functional traits in tropical regions concluded that the functional composition of tropical forest mammals is largely consistent among regions, likely due to the age and stability of these forests, as well as similarities in climate and day length [ 4 , 7 ]. These studies, used species richness to determine functional composition and diversity [ 8 , 9 ] rather than ‘occupancy’—defined as the proportion of sites occupied by a species [ 10 ].…”
Section: Introductionmentioning
confidence: 99%